Biophysical parameters and time to isolation of pulmonary veins with a novel cryoballoon: results of POLAR ICE study. (19th May 2022) - Martin, C; Tilz, RR; Anic, A; Defaye, P; Luik, A; Asmundis, C; Champ-Rigot, L; Iacopino, S; Sommer, P; Albrecht, E; Raybuck, JD; Wehrenberg, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Boston Scientific Introduction: Low nadir temperatures and long thaw times with cryoballoon ablation are associated with successful pulmonary vein isolation (PVI). Recently, a system that maintains uniform pressure and size has been introduced to improve catheter stability during cryoballoon ablation. The present results examine the relationship between cryoballoon time to isolation (TTI) and other biophysical parameters; time to -40ºC (TT-40), nadir temperature, time to thaw (TT0), and first pass isolation success in patients with paroxysmal AF (PAF). Methods: POLAR ICE, a prospective, non-randomized, multicenter (international) registry (NCT04250714), enrolled 400 patients across 19 centers, between Aug 2020 and May 2021. This study included any patients indicated for treatment of PAF with the POLARx cryoablation system. Cryodosing regimen was left to the operator and not specified by study protocol. Procedural characteristics, such as time to isolation (TTI), cryoablations per pulmonary vein, nadir temperature, and occlusion grade were recorded. PVI was confirmed via entrance block. Biophysical parameters for ablations longer than 120s were evaluated. Results: Data on 389 PVI procedures (n=2303 ablations) were collected. Of those ablations, 1914 (83%) had a duration of at least 120s and were included in this analysis. Isolation was attempted using the CB alone. TTI was reported in 1335 ablations with the majority (64%) occurring within 60s. Biophysical parameters and single shot success rates were examined based on TTI. Ablations with TTI<60s had significantly faster TT-40 (30.6±7.4s), lower nadir temperatures (-58.3±5.8ºC), longer thaw times (21.1±6.7s), and a greater proportion of grade 4 occlusions (88%) than longer TTIs or ablation with no TTI reported (Table 1). In TTIs<60s single shot success was 95%, significantly greater than TT≥60s, or No TTI. Procedure-related complications included: phrenic nerve palsy (0.5%), tamponade (0.5%), AV block (0.3%), stroke (0.3%), and transient ischemic attack (0.3%). Conclusions: These data suggest a correlation between cryoballoon biophysical parameters and single shot success. Good occlusion likely drives faster freeze and lower nadir temperatures, resulting in longer thaw times with this novel cryoballoon. Future research should examine the relationship between these parameters to drive optimization of cryoablation techniques and provide guidance toward improved workflow.